Presentation Methods of Children’s Work as an Effort to Develop Speaking Skills of 5-6 Years In ABA Kindergarten 03 BOJA - Lestari, Ika Puji (Jurusan PGPAUD FIP UNNES, 2017)
Presentation method of the work is a method of presentation by using the work of the child as a medium in the delivery of material to his friends. Speaking skills are very important for the individual to the task of further development in the life of the community and in the world of work, thus honing the ability of speaking skills is very important. The aim of this research is to develop children's speaking skill, including linguistic aspects (pronunciation, vocabulary, and sentence formation) and non-linguistic aspects (courage, fluency, and body expression), and also to find out the great improvement of speech skills of 5- 6 years in Kindergarten ABA 03 BOJA. The type of this research is experimental research with one group pretest and posttest design. The research was done by giving 12 treatments / treatment consisting of 37 children in group B. The data analysis technique used was descriptive analysis with SPSS 16 application. The result of the research using the method of presentation of the work before being given the action showed the ability of speaking skills of children with category Not Developed (BB) 12 children with percentage of 32.43%, category Started Developing (MB) is 13 children with percentage of 35.13%, Developed As Expected (BSH ) Of 10 children with a percentage of 27.02%, and Very Good Developing (BSB) are 2 children with 5.4% percentage, and after being given Action category Developing (MB) 12 children with percentage of 32.43%, Expanding As Expected (BSH) 18 children with a percentage of 48.64%, and the category Very Good Developing (BSB) is 7 children with percentage 18.91%. Based on the result of the research shows that the method of presentation of the work improves the speaking ability of children aged 5-6 years in kindergarten ABA 03 Boja which before given the action that is 32.42% and after given the action that is 67.55%.